I could be, you could be - Owen, Karen, 1970-; Barroux (Oxford [England] ; Cambridge, MA : Barefoot Books, 2011)
Illustrations and rhyming text encourage readers to picture themselves becoming a variety of people and things, from an astronaut to an elephant to an alien. Includes instructions for making masks.
003-005.
Keywords: Stories in rhyme; Identity (Philosophical concept) -- Juvenile fiction; Imagination -- Juvenile fiction; Identity -- Fiction; Imagination -- Fiction